EFL Students’ Perceptions of AI-Powered Feedback in Academic Writing: A Qualitative NVivo Study - Fadillah, Ridha; Saadillah (ELITE JOURNAL, 2025)
Artificial intelligence (AI) is increasingly integrated into English as a Foreign Language (EFL) pedagogy, yet little is known about how learners in Southeast Asia perceive its feedback. This study explored Indonesian undergraduates’ perceptions of AI-powered feedback in academic writing. Data were collected through semi-structured interviews with seven students and analyzed thematically using NVivo 12. Four themes emerged: (1) AI was valued for grammar and vocabulary support, though suggestions for coherence and organization were often contested; (2) students reported ambivalent emotions—confidence and motivation alongside anxiety about dependency; (3) a trust hierarchy was evident, with AI trusted for surface-level corrections but distrusted for content-level changes; and (4) learners selectively blended AI and teacher feedback, positioning instructors as the final authority. These findings extend feedback literacy to AI contexts and refine the Technology Acceptance Model, suggesting the need for critical feedback literacy training and institutional policies on ethical AI use.